THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES AS A FACTOR OF INCREASING THE EFFECTIVENESS OF EDUCATION (Academicia Globe: Inderscience Research, 2023)
In the given article, it is stated to conduct educational activities with the help of information technologies in the educational process provides to develop creative skills in students, and the use of modern information media serves facilitates to form practical skills and competencies.